Seksualitas dan Perkembangan Gamet Sponge Laut Aaptos aaptos Schmidt - Haris, Abdul; Soedharma, Dedi; Zamani, Neviaty P.; Pariwono, John I.; Rachmaniar, Rachmaniar (Jurnal Natur Indonesia, 2012)
This research was aimed to know the characteristics of gamet development of marine sponge Aaptos aaptos living in tropical waters of Barrang Lompo Island, Spermonde Archipelago, South Sulawesi. In order to know gamet development, it was conducted three periods of sample collection at each moon phase. After sample collection, the specimen were put into tissue cassette and then were removed to fixative solution of FAACC (for 100 mL = 10 mL formaldehyde solution of 37–40%: 5 mL glacial acetic acid: 1.3 g calcium chloride dihydrate: 85 mL destilate water) for +48 hours, and then were removed to 70% alcohol for temporary storage before doing histological preparation following standard procedure. Sexuality of marine sponge Aaptos aaptos living in Barrang Lompo Island is gonochoric. Spermatocyt developed in spermatic cyst, while oocyt developed in the mesohyl. Stage of male gamet development was divided into four phases i.e. spermatocyt I phase, spermatocyt II phase, spermatocyt III phase, and spermatocyt IV (spermatid) phase, similarly, female gamet develop- ment was divided into four phases i.e. oocyt I phase, oocyt II phase, oocyt III, oocyt IV phase. Each phase of gamet development had specific characterstics different from among each others.